ASPECTS OF POLICY FOR STIMULATING THE DEVELOPMENT OF THE AGRICULTURAL PRODUCTS MARKET OF UKRAINE ON AN INNOVATIVE BASIS - VASYLTSIV, Taras; KUNYTSKA-ILIASH, Marta; MAKSYM, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The study analyzes the issues of formation and implementation of state policy aimed at ensuring the development of the agricultural products market in Ukraine. Special attention is focused on the problems of the innovative vector of progress in the studied market. Accordingly, the purpose of the publication is defined as the elaboration of policy aspects for stimulating the development of the Ukrainian agricultural products market on an innovative basis. The article examines the current state of innovativeness and innovation activity in the domestic agricultural products market, which remain at a low level. This is manifested in the slow modernization of production, limited digitalization of the agricultural sector, and insufficient implementation of research results into practice, which hinders the increase of economic efficiency and reduces the competitiveness of Ukrainian agricultural products in both domestic and international markets. The necessity of intensifying state policy for stimulating the innovative development of the agricultural sector is substantiated through the use of a set of instruments, including financial support for modernization, concessional lending and grants, the development of digital technologies and “smart farming” systems, support for agrotechnological startups and organic production, certification of products in accordance with international quality standards, as well as the creation of clusters uniting science, business, and the state. It is proved that the implementation of these measures will contribute to the increase of productivity and quality of agricultural products, expansion of export potential, rational use of resources, and strengthening of food security, which in combination will ensure the consolidation of the agricultural sector’s position in the national economy and accelerate its integration into global markets.